2017
DOI: 10.1111/jdi.12617
|View full text |Cite
|
Sign up to set email alerts
|

Circulating ferritin concentrations and risk of type 2 diabetes in Japanese individuals

Abstract: Aims/IntroductionHigher iron storage has been linked to an increased risk of type 2 diabetes, but little is known about the mediator of this association. Here, we prospectively investigated the association between circulating ferritin, a marker of iron storage, and the incidence of type 2 diabetes among Japanese individuals.Materials and MethodsThe participants were 4,754 employees who attended a comprehensive health check‐up in 2008–2009 and donated blood for the study. During 5 years of follow up, diabetes w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
24
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 49 publications
3
24
0
2
Order By: Relevance
“…Several previous studies have indicated that elevated levels of circulating ferritin are associated with disrupted glucose and lipid metabolism, which is observed in T2DM[1417], gestational diabetes[18, 19], IR[20, 21], β-cell dysfunction[22], obesity[2327], dyslipidemia[20], CVD[28, 29], and MetS[3, 30]. This study also showed that subjects with dyslipidemia and diabetes had higher serum ferritin levels than subjects without dyslipidemia and diabetes in both genders.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several previous studies have indicated that elevated levels of circulating ferritin are associated with disrupted glucose and lipid metabolism, which is observed in T2DM[1417], gestational diabetes[18, 19], IR[20, 21], β-cell dysfunction[22], obesity[2327], dyslipidemia[20], CVD[28, 29], and MetS[3, 30]. This study also showed that subjects with dyslipidemia and diabetes had higher serum ferritin levels than subjects without dyslipidemia and diabetes in both genders.…”
Section: Discussionmentioning
confidence: 99%
“…As an iron-storage protein, serum ferritin is used to evaluate the status of common diseases, such as iron-deficiency anemia [21, 27], and hereditary and acquired iron overload conditions, such as hereditary hemochromatosis, thalassemia, hemoglobinopathy and chronic transfusion therapy [31]. Serum ferritin is also recognized as an acute phase marker of inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…As previously described 38,39 , we identified a total of 357 new-onset T2D cases over a 5-year follow-up period. We randomly selected two controls for each case by using incidence density sampling, which involves matching each case to each risk set from cohort subjects under follow-up at the time of case occurrence 40 .…”
Section: Methodsmentioning
confidence: 99%
“…In the presence of inflammation, elevated SF may conceal poor iron status [2, 5, 9, 14]. SF has also been identified as a predictor of diabetes [1518], metabolic syndrome [10, 19] and cardiovascular events [2022]. The prevention and management of elevated SF is therefore a strategy in the prevention of these conditions [10, 18, 22].…”
Section: Introductionmentioning
confidence: 99%